(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the influence of the 4P marketing mix (product, price, place, and promotion) on performance in the traditional channel in Tegal, which can be applied to increase the sales of grocery vendors after identifying the most important points of the 4P marketing mix to compete with modern channels and also the emerging e-commerce with online platforms. This study uses a survey method by collecting data from respondents related to the traditional channel. The results show that the marketing mix has a significant impact on performance in the traditional channel. Product, price, place, and promotion both partially and simultaneously have a positive and significant impact on performance in the traditional channel. This research contributes to the development of marketing strategies in traditional channels and provides recommendations for companies to improve performance in traditional channels. In addition, it can provide an up-to-date picture of the competition that is not only occurring in offline stores but is also beginning to develop with online stores that allow traders to start their businesses by selling in physical stores while also enabling customers to place orders through WhatsApp, social media, or other simple tools that make it easier for customers to buy online.